Atlantic Salmon (Salmo salar) Performance Fed Low Trophic Ingredients in a Fish Meal and Fish Oil Free Diet - Kousoulaki, K.; Sveen, L.; Norén, F.; Espmark, Å. (Frontiers in Physiology, 2022)
To evolve fish farming in an eco-efficient way, feed production must become less dependent on forage fish-based ingredients and make more use of low trophic level organisms, including microalgae, higher plants, as filter feeding organisms and other ingredients with low competition to established food value chains. Diets nearly free of fish meal and fish oil are not a novelty but are often composed of complex mixtures, containing supplements to meet the farmed animal’s nutritional requirements. Sustaining a growing aquaculture production, maintaining at the same time fish health, welfare, and profitability, and meeting strict environmental and food safety demands, is challenging and requires new technologies, great investments, and more knowledge. A benchmarking feeding trial was performed to demonstrate the main effects of four low trophic raw materials on Atlantic salmon (Salmo salar) growth, metabolism, skin health and fillet quality. To this end, a diet was produced to contain commercially relevant levels of fresh high quality organic FM and FO and was used as a control in the trial (FMFO). Heterotrophically produced Schizochytrium limacinum biomass was used to replace organic FO (HM diet). Spray dried cell wall disrupted biomass of the phototrophically cultured diatom Phaeodactylum tricornutum replaced partly FM and FO (PM diet). Black soldier fly (Hermetia illucens) larvae meal and tunicate (Ciona intestinalis) meal, were used to produce the diets BSFL and TM, respectively, replacing large parts of FM as compared to the FMFO. A fifth test diet was produced combining all test raw materials and removing all FM and FO (0FM0FO diet). All test ingredients were well accepted sustaining high growth rates (TGC values near 4) and feed efficiency (FCR values below 0.9) in salmon showing good gut health and normal metabolic responses. However, none of the treatments reached the growth performance of FMFO. Additional differences between test and control treatments were identified in dietary nutrient apparent digestibility, fish biometrics, blood metabolites and fillet and skin composition. Extensive raw material and dietary chemical characterisation was performed to provide insight on potential shortcomings in the novel low trophic level ingredients which can possibly be overcome combining complementary raw materials.